Formation of a counter-rotating stellar population in the Large Magellanic Cloud: a Magellanic triplet system?. (6th August 2018) - Armstrong, B; Bekki, K
ABSTRACT: The Large Magellanic Cloud is observed to have a counter-rotating stellar population in its disc, which has not been reproduced in previous simulations of the Magellanic system. We propose a new scenario in which the origin of this counter-rotating stellar population is the result of a minor retrograde merger with another dwarf galaxy more than 3 Gyr ago, and investigate this scenario using our hydrodynamical simulations. Our simulations show that such merging can result in a counter-rotating stellar component and a co-rotating gaseous component. We show that this counter-rotating population would not be radially concentrated, but found throughout the Large Magellanic Cloud. The thin disc of the Large Magellanic Cloud is thickened by the merging. We suggest that the Magellanic Clouds were originally a triplet system containing this companion galaxy. We then discuss previous observations of the Magellanic Clouds in the context of a triplet dwarf system, and discuss how such a merger could occur.